2018
DOI: 10.5765/jkacap.2018.29.2.40
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Effectiveness of the Peer Relationship Enhancement Program in Adolescents at Risk for Internet and Smartphone Addiction

Abstract: The purpose of this study is to evaluate the preliminary effects of the Peer Relationship Enhancement Program in adolescents deemed to be in an at-risk group for Internet and smartphone addiction. Methods: The study group consisted of 33 adolescent participants (24 boys and 9 girls) at risk of Internet and smartphone addiction in small and medium-sized cities. The subjects participated in 8 consecutive sessions of the Peer Relationship Enhancement Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…For example, Tzeng (2010) suggested that college students’ self-discrepancy in Internet use symbolizes some psychological or behavioral dissonances. The enhancement of peer relationship skills can help to reduce the actual-ideal discrepancy in adolescents, which may, in turn, reduce their risk for Internet and smartphone addiction ( Kim T.-H. et al, 2018b ). In addition, Li et al (2011) found that actual-ideal self-discrepancy has a direct impact on pathological gaming.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Tzeng (2010) suggested that college students’ self-discrepancy in Internet use symbolizes some psychological or behavioral dissonances. The enhancement of peer relationship skills can help to reduce the actual-ideal discrepancy in adolescents, which may, in turn, reduce their risk for Internet and smartphone addiction ( Kim T.-H. et al, 2018b ). In addition, Li et al (2011) found that actual-ideal self-discrepancy has a direct impact on pathological gaming.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers can include them and examine their unique roles. Second, although parents and teachers are the most important adults in adolescents’ lives [15,16], peer relationships may also play a crucial role in adolescents’ addictive behaviors [63] and future studies can simultaneously examine and compare the unique roles of peers, parents and teachers in PMPU. Third, the cross-sectional design of this study indicates that causal descriptions among main variables are only based on theoretical assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual spaces can be attractive to adolescents with poor peer relationships. It enables people to escape their dissatisfaction with themselves in the real world (Kim et al, 2018).…”
Section: Depressionmentioning
confidence: 99%